Influence of electrophysical water treatment on the process of beverages saturation - Nescuba, Oleksiy; Chepeliuk, Olena (My University, 2018)
The content of carbon dioxide, which is actively used by producers of carbonated beverages as a preservative, acidity regulator and antioxidant, significantly affects the quality of finished products. The possibility of changing the ph value, which affects the balance between carbon dioxide, bicarbonate and carbonate during saturation, by electrophysical treatment of water was considered. Industry produces various variants of electrolysers, but they are not suitable for saturation of drinks. Therefore, the development of an appropriate design is an urgent task. It is expedient to carry out the process of saturation simultaneously with the electrophysical treatment of pre-prepared (cooled and deaerated) water. The parameters that influence the efficiency of electrophysical treatment and the quality of finished products are the voltage, the voltage-ampere characteristic, the mutual placement of the electrodes, the duration of activation, the degree of mineralization of the solution. The influence of material of equipment, including electrodes, on the content of metals in the carbonated beverages is also taken into account. Electrodes in the process of operation should not experience electrochemical destruction. It is expedient to make an anode from a titanium, a cathode - from a corrosion resistant steel AISI 321.
Keywords: сатурація; напої; електрофізичне оброблення; рівень pH; сатурация; напитки; электрофизическая обработка; уровень pH; saturation; beverages; electrophysical treatment; pH value; кафедра машин і апаратів харчових та фармацевтичних виробництв